Charge density waves and degenerate modes in exfoliated monolayer 2H-TaS2. (2020) - Zhang, Duan; Wu, Yecun; Su, Yu-Hsin; Hsu, Ming-Chien; Coileain, Cormac O; Cho, Jiung; Choi, Miri
No abstract available